Identification of isomorphism in epicyclic gear trains- A Bocher's approach. (2020) - Mustafa, Jiyaul; Hasan, Ali; Khan, R.A.
Abstract: The identification of isomorphism among epicyclic gear trains (EGTs) and their mechanisms has great area of research for the last few years. In this paper, a novel approach based on Bocher's equation is presented to identifying all distinct EGTs with different links and degree of freedoms. It is basically based on the connectivity matrices and the absolute sum of polynomial coefficient which identifying isomorphism in EGTs. Finally, the proposed method was examined on the basis of various examples from 4, 5, 6, and 8-links one-dof and 6-links two-dof EGTs. All examples have been found satisfactory results with existing literature.